2014
DOI: 10.5812/ircmj.10016
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Fatal and Nonfatal Road Crashes in Iran

Abstract: Background:Road traffic injuries are among the leading causes of death in the world and Iran.Objectives:The aim of this study was to assess the role of age, sex, education, and time of accident on human casualties and mortalities of road crashes in Iran.Materials and Methods:This study was based on data gathered by Iranian Police Department from the records of road crashes from April 4, 2008 through April 4, 2009. Road crashes are categorized into three types: with no human casualties, with injuries, and with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 25 publications
(32 reference statements)
6
16
0
Order By: Relevance
“…However, mortality rate was 1.35% and 1.26% higher in stormy and foggy weather respectively in comparison to clear weather (92). In addition to this, it was reported that 82.8% of crashes occurring during winter, 60.2% during autumn and 35.8% during summer are associated with mortalities (93). …”
Section: Resultsmentioning
confidence: 89%
“…However, mortality rate was 1.35% and 1.26% higher in stormy and foggy weather respectively in comparison to clear weather (92). In addition to this, it was reported that 82.8% of crashes occurring during winter, 60.2% during autumn and 35.8% during summer are associated with mortalities (93). …”
Section: Resultsmentioning
confidence: 89%
“…The odds of fatal accidents were higher in autumn than in winter. Seasons exert a significant impact on road accidents and deaths (9,21). In a study conducted in Iran, the highest and the lowest death rates were found out to be in winter and in summer, respectively (21).…”
Section: Discussionmentioning
confidence: 99%
“…Seasons exert a significant impact on road accidents and deaths (9,21). In a study conducted in Iran, the highest and the lowest death rates were found out to be in winter and in summer, respectively (21). A study conducted in the United States showed that the severity of accidents was higher in autumn and in winter than in spring (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of traffic accident mortality, Iran is among the world's leading countries (1). According to the world health organization (WHO), road crashes are the ninth most frequent cause of death, especially in countries with low or average income (2).…”
Section: Introductionmentioning
confidence: 99%